Chemical signatures of polycyclic aromatic hydrocarbons in the emissions from in situ oil burns. (November 2022) - Yin, Fang; Gao, Chen; Song, Zhibo; Han, Yuling; He, Zhiwei; Zhang, Li; Su, Penghao; Feng, Daolun; Yang, Tao; Fu, Jie
Abstract: This study characterized the parent and alkylated polycyclic aromatic hydrocarbons (PAHs) in gaseous and particulate emissions from the in situ burning (ISB) of oils. The experimental results indicate that the burning of the heavy oil produced the most PAH emissions because of its longest burning time. In addition, the parent PAHs mainly exist in the particulate phase, while alkylated PAHs mostly accumulate in the gaseous phase. In particular, the diagnostic-ratios of PAHs with great stability in both gaseous and particulate emissions from ISB are identified by comparing the laboratory and field data. The presences of bell-, slope- and V-shaped distribution patterns of alkylated PAHs in the emissions precisely indicate their sources to be petrogenic and pyrogenic processes occurring during ISB. The formation of 2-methylanthracene during ISB is confirmed. The overall findings are expected to provide a prospective protocol to characterize PAH pollution from ISB emissions in case of oil spills. Graphical abstract: Unlabelled Image Highlights: Parent PAHs mainly exist in the particulate phase but alkylated PAHs are predominant in the gaseous phase. Source-specific ratios of ISB PAHs in gaseous and particulate phases were summarized. Distribution patterns of alkylated PAHs are reliable for characterizing ISB emissions. 2-Methylanthracene is a validated indicator for identifying ISB process.